High Performance PCC-DMT System Based on Hybrid Multi-Wavelet Functions (University of Thi-Qar Journal for Engineering Sciences, 2010)
In this paper a scheme is proposed to improve the Bit Error Rate (BER) performance for Discrete Multi-Tone (DMT) system in wireless channel. The conventional DMT system is based on Fast Fourier Transform (FFT). The proposed system is based on Hybrid Multi-Wavelet Transform (HMWT). The HMWT is mixed between FFT and Multi-Wavelet Transform (MWT). The Inter-Carrier Interference (ICI) in DMT system due to Doppler spread is reduced by using Polynomial Cancellation Coding (PCC). Simulation results are done in three different types of channels: Additive White Gaussian Noise (AWGN) channel, flat fading channel and selective fading channel. The results show that the PCC-DMT system based on HMWT achieves better performance than the PCC-DMT system based on FFT and the PCC-DMT system based on MWT in all channels types.